Analysis of the characteristics of four severe aircraft icing events in Southwest China during the winter of 2023 - Wen, Ying; Wang, Chao; Wang, Ziyi; Wang, Runying; Yuan, Min (Frontiers in Earth Science, 2025)
This study investigates four severe aircraft icing cases in Southwest China during the winter of 2023, focusing on their circulation patterns and cloud macro-characteristics. The results indicate that the meridional Yunnan-Guizhou quasi-stationary front (YGQSF) drives these severe icing. The synergistic interaction between the cold Mongolian high and Northeast China Cold Vortex intensified East Asian meridional circulation, triggering strong convergence of warm-moist and dry-cold air over Southwest China. The terrain-forced updraft near the front continuously transports moisture to 700 hPa, where the airflow shifts to westerlies, inducing the formation of convergent cloud clusters and horizontal cloud expansion. Meanwhile, a persistently maintained closed vertical circulation cell on the cold side may play a vital role in sustaining cold air masses and frontal cloud clusters over Southwest China. Furthermore, the temperature inversion layer (within 850–700 hPa) east of YGQSF maintained supercooled liquid water reservoirs and limited ice-phase particles via stable “warm-over-cold” stratification and suppressed convection. Besides, analysis of cloud macro-characteristics showed that the frontal icing-related cloud coverage reached 100%, with all cases occurring in supercooled clouds oriented from southwest to northeast. The cloud top temperatures ranged from −25°C to −10°C, and the cloud top heights exhibited a “higher in the north, lower in the south” distribution, generally between 5 and 7 km. These results provide a thermodynamic framework for forecasting severe winter aircraft icing in Southwest China.